Struktur dan Makna Penyajian Wayang Kulit Purwa Banjar - Novyandi Saputra (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2016)
AbstractResearch manifold-descriptive qualitative attempts to describe and interpret the structure of Wayang Kulit Purwa Banjar performances in the village Barikin, South Kalimantan. Through insider approach, researchers used observation, interview and documentation to collect data and analyze it-hermeneutical interpretive. The structure is a puppet show has three babakan/main parts: opening, contents and closure. The structure of the note also contains the implicit meaning and value. Meaning and religious value being the foremost.Keywords: banjar purwa puppet, barikin village, forms of performance, meaning